Implementation of LUC Algorithm-Based Cryptography in Document File Protection - Muhammad Sabiq; Surya Guntur (NEXCORE: Journal of Computer Science & Intelligent Systems, 2026)
In this study, the authors implement the LUC cryptographic algorithm for securing file messages. Cryptography is a scientific discipline that explores the art and methods of ensuring that a message cannot be interpreted by unauthorized parties. The purpose of this research is to apply the LUC algorithm in a user-friendly manner while utilizijng hexadecimal number system conversion so that the resulting ciphertext becomes more complex to decipher and the ciphertext file size is not excessively large, since the LUC algorithm typically produces ciphertext much larger than its plaintext. The test results show that the developed cryptographic application is easy to use (user-friendly) because the key generation process is performed automatically. The encryption process using the LUC conversion algorithm (by adding hexadecimal number conversion) produces more randomized ciphertext and keeps the encrypted file size relatively small.